Portfolio assessment as an alternative evaluation method in young learner's English classes - Xudoyqulova Feruza (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
In modern English as a Foreign Language (EFL) classrooms, assessment plays an important role in monitoring learners’ progress and improving teaching effectiveness. Traditional assessment methods such as written tests and examinations are often limited in evaluating young learners’ overall language development. Portfolio assessment, as an alternative evaluation method, provides a more comprehensive and learner-centered approach by collecting students’ work over a period of time. This paper aims to explore the role of portfolio assessment in young learners’ English classes and examine its effectiveness in supporting language learning. It focuses on how portfolio assessment encourages learner autonomy, creativity, self-reflection, and active participation in classroom activities. Based on qualitative and quantitative approaches, the study investigates teachers’ use of portfolios, the types of activities included in portfolios, and the impact of portfolio assessment on learners’ motivation and language achievement. The findings suggest that portfolio assessment helps young learners become more confident in using English, improves their speaking, writing, reading, and listening skills, and creates a positive and supportive learning environment. The paper concludes with practical recommendations for teachers on how to effectively implement portfolio assessment in young learners’ EFL classrooms.